Screening for Pentachlorophenol-degrading microbial candidates for bioaugmentation of anaerobic waste water treatment and analysis of microbial community in anaerobic bioreactors exposed to Pentachlorophenol and its metabolic intermediates - Tan, Serene Xiao Lin (2014)
Pentachlorophenol (PCP) is a recalcitrant compound that can sometimes be found in waste water. Improper disposal of PCP has led to its accumulation in the environment. Bioaccumulation of PCP not only poses a threat to human but its high toxicity and low biodegradability causes inhibition to bioremediation processes, making it difficult to eliminate from contaminated sites.